Sanguis draconis, a Dragon's Blood Resin, Attenuates High Glucose-Induced Oxidative Stress and Endothelial Dysfunction in Human Umbilical Vein Endothelial Cells. (2nd June 2014) - Chang, Yi; Chang, Ting-Chen; Lee, Jie-Jen; Chang, Nen-Chung; Huang, Yung-Kai; Choy, Cheuk-Sing; Jayakumar, Thanasekaran
Abstract : Hyperglycaemia, a characteristic feature of diabetes mellitus, induces endothelial dysfunction and vascular complications by limiting the proliferative potential of these cells. Here we aimed to investigate the effect of an ethanolic extract of Sanguis draconis (SD), a kind of dragon's blood resin that is obtained from Daemonorops draco (Palmae), on human umbilical vein endothelial cells (HUVEC) under high-glucose (HG) stimulation and its underlying mechanism. Concentration-dependent (0–50  μ g/mL) assessment of cell viability showed that SD does not affect cell viability with a similar trend up to 48 h. Remarkably, SD (10–50  μ g/mL) significantly attenuated the high-glucose (25 and 50 mM) induced cell toxicity in a concentration-dependent manner. SD inhibited high glucose-induced nitrite (NO) and lipid peroxidation (MDA) production and reactive oxygen species (ROS) formation in HUVEC. Western blot analysis revealed that SD treatments abolished HG-induced phosphorylation of extracellular signal-regulated kinase 1/2 (ERK 1/2), nuclear transcription factor, κ B (NF- κ B), VCAM-1, and E-selectin, and it also blocked the breakdown of PARP-116 kDa protein in a dose-dependent manner. Furthermore, we found that SD increased the expression of Bcl-2 and decreased Bax protein expression in HG-stimulated HUVEC. Thus, these results of this study demonstrate for the first time that SD inhibits glucose induced oxidative stress and vascular inflammation in HUVEC by inhibiting the ERK/NF- κ B/PARP-1/Bax signaling cascade followed by suppressing the activation of VCAM-1 and E-selectin. These data suggest that SD may have a therapeutic potential in vascular inflammation due to the decreased levels of oxidative stress, apoptosis, and PARP-1 activation.